Indian Terracotta of Gorakhpur and Bindi(Tikuli) in Balia and women artisan in the digital era: A Case study on the Traditional Bindi Handicraft in Uttar Pradesh - Uma Shankar Yadav Yadav; Dr. Ravindra Tripathi; Dr. Gyan Praksh Yadav (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
The present paper aims to understand the current situation of the terracotta industry of Gorakhpur that have got GI geographical indication, and Ponchmura of West Bengal that has led the tradition and heritage of Indus valley civilization in 2700 BC but also revving and maintains our culture in this digital era and in this work India women have participated but we have to know that there is need of improving their socioeconomic women workers to recommend fewer measures for the inclusive growth(digital growth, financial growth, economic social political and sustainable growth) of the entire society by understanding their perspectives. This paper is going to help us understand and study about the terracotta industry and the performance of women in this sector along with the impact of covid and digital technology in this industry. This is also studying the development of women artisans through policymakers and planners and also helps us to give an idea about the importance of building women’s capacities to improve their socio-economic status, which can directly improve their skills, personality, and self-concept, leadership, and income,